Factors contributig to tax noncompliance amongst property developers in Malaysia: a survey of tax auditors' opinions from the corporate tax department of the inland revenue board Malaysia / Rohana Salleh - Salleh, Rohana (2013)
Income tax is the main source of income to the nation. In 2011, Inland Revenue Board of Malaysia (IRBM) became the biggest contributor to the total income of the Federal Government, which hold about 59.11% with the value of RM185.42 billion (IRBM, 2011). Out of this values, it shows that corporate taxpayers were contributed a very prominent amount which is RM55.08 billion carrying 50.25% over the total percentage of the total collections (IRBM, 2011). As a result, it is clearly shown that corporate taxpayers are the biggest contributor to the government's revenue followed by petroleum companies and continued by individual taxpayers. The main objective of this study is., to outline the factors that contribute to tax noncompliance of property developers in Malaysia. The study is mainly focus on noncompliance of final accounts that prepared by taxpayers in developers business. The result of the study is collected from findings of questionnaires' survey as well and supported with the findings from two real cases that come from the field audit. This study has found that taxpayers who are not representing by the Big4 audit firms seemed to be not to comply with the public ruling and regulations of IRBM. The survey have found that 50% of tax auditors agreed that less than five companies with their audit cases had paid up share capital more than 2.5 million. This can be simplified as most of the company that the tax auditors auditing the cases and the final accounts come from small and medium enterprise. The survey also found that taxpayers intend to not comply with the preparation of final accounts according to Public Ruling No.l/2009. Failure to prepare the final accounts will cause taxpayers paying additional tax including the amount of penalty. They also agreed that by imposing the additional penalty like 450/0 on tax findings will reduce non-compliance of final accounts rate that was prepared by tax preparers. The findings from this study recommend CTD to implement an intensification of enforcement programs, imposition of penalty to non-compliance of final accounts and collaboration with third parties in the way to reduce non-compliance of preparation of final accounts amongst property developers in Malaysia.